2015
DOI: 10.1016/j.bjp.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of larvicidal activity of a nanoemulsion of Rosmarinus officinalis essential oil

Abstract: a b s t r a c tNanotechnology has emerged as a promising area for innovative products, including insecticides. Dengue is a tropical disease which is considered a critical health problem in developing countries, due to negative impacts to the environment caused by synthetic chemicals used for vector control (Aedes aegypti). Thus, developing of natural products based insecticidal are considered very promising. On this context, the aim of the present study was to obtain an O/W nanoemulsion containing Rosmarinus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(79 citation statements)
references
References 16 publications
(22 reference statements)
9
70
0
Order By: Relevance
“…Parallel to our findings, Duarte et al . () reported an increase in the mean of droplet size of Rosmarinus officinalis EO nanoemulsion after 7 days of preparation. However, it was maintained below 200 nm, and PDI was reduced during 30 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Parallel to our findings, Duarte et al . () reported an increase in the mean of droplet size of Rosmarinus officinalis EO nanoemulsion after 7 days of preparation. However, it was maintained below 200 nm, and PDI was reduced during 30 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…The larvicidal activity of a nanoemulsion of R. officinalis EO was evaluated (Duarte et al ). Rosemary nanoemulsion presented low polydispersity and mean droplet below 200 nm.…”
Section: Discussionmentioning
confidence: 99%
“…33 Nanoemulsions from essential oils are also effective carriers for antiviral substances acting on vector-borne diseases. 34,35 Several polymers such as poly(lactide-co-glycolide) (PLGA), poly(D,L-lactic acid) (PLA), polyglycolide, polycaprolactone (PCL), poly(D,L-lactide), chitosan and PLGA-polyethylene glycol (PEG) were developed for passive and ligand-targeted delivery of therapeutic drugs. 36,37 In particular, it was observed that carriers for antiviral drugs exert the antiviral activity of the encapsulated molecules, indicating that direct interaction between the nanoparticles and the virus may inhibit viral attachment to cells.…”
Section: Antiviral Drugsmentioning
confidence: 99%
“…aegypti larvae, showed a mortality levels of 80 ± 10 and 90 ± 10% after 24 and 48 h, respectively. 35 The green synthesis of metal nanoparticles has been proposed as an alternative to chemical methods, particularly through the use of fungi, since that the benign environment and renewable source of fungi act as reducing agents in the preparation of metal nanoparticles. These kinds of nanoparticles have exhibited efficacy against mosquito larvae (e.g., Aedes, Culex and Anopheles).…”
Section: Nanoinsecticide Against Mosquitoesmentioning
confidence: 99%